Analysis Of The Judge's Decision On The Marriage Legalization Case Number: 143/Pdt.P/2021/Pa Sak At The Religious Court Of Siak Sri Indrapura In The Perspective Of Islamic Law - Taufik Taufik; Akbarizan Akbarizan; Hidayatullah Ismail (International Journal of Law and Society, 2025)
There are two types of marriage guardians: first, nasab guardians, namely guardians whose guardianship rights are based on blood relations. Such as, his biological parents, or also wali aqrab and ab'ad (closest or distant relatives). Second, the wali hakim is a guardian whose guardianship rights arise because the bride's parents refuse (adhal) or are absent, or for other reasons that physically exist but the guardianship rights do not exist. The emergence of the Itsbat Nikah provision is also related to the issue of the status of marriage registration. There are two views on the issue of the status of marriage registration, the first view states that marriage registration is only an administrative requirement, not a condition for the validity of a marriage, so marriage registration is only a process of obtaining evidence that a marriage has been carried out by someone, while the second view states that marriage registration is a valid condition for marriage. In this discussion, the author focuses on the consideration of judges who grant itsbat nikah cases where the previous marriage was held using an unofficial guardian or not the KUA head. This is not in accordance with article 23 of the Compilation of Islamic Law “(1) The new guardian judge can act as a marriage guardian if the nasab guardian is absent or impossible to present or his residence is unknown or absent or adlal or reluctant”. The Applicant's marriage guardian in the marriage contract was another person (a local community leader named Selan) due to the Applicant's non-Muslim biological father. The judge considered it as follows: that a kiyai, cleric or community leader who acts as a marriage guardian in Islamic law is known as wali muhakkam, namely someone who is appointed by the prospective husband and wife to act as a guardian in their marriage.